Los trastornos psicomotores y su incidencia en la lectoescritura de los niños y niñas de la escuela de educación básica Francisco Campo de la parroquia Tenta cantón Saraguro provincia de Loja, periodo 2014 - Abad Muñoz, Mabel Karina (2015)
The research done on the topic: THE PSYCHOMOTOR DISORDERS AND THEIR IMPACT ON THE LITERACY OF CHILDREN AND GIRLS OF THE SCHOOL OF BASIC EDUCATION FRANCISCO CAMPO OF THE Saraguro PARISH TENTA CANTON PROVINCE OF LOJA, PERIOD 2014, constitutes a significant contribution to the educational training that today require students pre-school education. The structure of the thesis is exposed to from its scientific methodology according to the variables and the results as well as field research along with the check of objectives, findings and recommendations. In the investigation, it was review the results of the application of the instruments as is the survey and the test of Oseretski. The overall goal that guided this research was: to raise awareness to the teachers on the importance of prevention of the psychomotor development within the teaching-learning process of children in the School of Basic Education Francisco Campos of the Saraguro Parish Tenta Canton province of Loja, period 2014. The theoretical part was oriented from the variables: psychomotor disorders and literacy. The methods used were the scientific, descriptive, analytical, inductive, deductive, statistical. The instruments were applied to 8 girls and 12 children and two teachers, from the point of the survey and the test of Oseretski. Then they compare the objectives and establish the main conclusions and recommendations. Among the conclusions the teachers demonstrating, that the psychomotor development in girls and boys is essential for the initial processes of pre pre reading and writing.